Science-based assessment of source materials for cell-based medicines: report of a stakeholders workshop. (29th November 2018) - Stacey, Glyn; Andrews, Peter; Asante, Curtis; Barbaric, Ivana; Barry, Jaqueline; Bisset, Louise; Braybrook, Julian; Buckle, Robin; Chandra, Amit; Coffey, Peter; Crouch, Sharon; Driver, Philip; et al.
Human pluripotent stem cells (hPSCs) have the potential to transform medicine. However, hurdles remain to ensure safety for such cellular products. Science-based understanding of the requirements for source materials is required as are appropriate materials. Leaders in hPSC biology, clinical translation, biomanufacturing and regulatory issues were brought together to define requirements for source materials for the production of hPSC-derived therapies and to identify other key issues for the safety of cell therapy products. While the focus of this meeting was on hPSC-derived cell therapies, many of the issues are generic to all cell-based medicines. The intent of this report is to summarize the key issues discussed and record the consensus reached on each of these by the expert delegates. Lay abstract: Cell therapies utilize cells provided with the consent of donors to generate preparations to restore tissue function in patients who have suffered injury or have some other disease. These preparations are diverse and often highly complex which means that that their manufacture requires great attention to assure they are safe and effective. This paper describes a conversation among experts in the field exploring these safety issues and what they mean for manufacturers.